Impacts of three pesticides on arthropod biodiversity in brinjal agro-ecosystem (International Journal of Agricultural Research, Innovation and Technology, 2018)
A field study was conducted to find out the impact of three selected pesticides on arthropod biodiversity in brinjal agro-ecosystem during 2011-2012 at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU). Twenty-six arthropod species were observed through visual searching method out of which 18 were insect pest species (from 14 families under 8 orders) and 8 were natural enemies (from 8 families under 6 families). Twenty one species of surface dwelling arthropods were caught in pitfall traps method, 12 of them were insect pest species (from 11 families under 8 orders) and 9 were natural enemies (from 9 families under 5 orders). Formicidae was the most abundant family among them. Bacillus thuringiensis (Bt) and Tracer 45SC (Spinosad) were less harmful to arthropod pest species as well as natural enemies in the brinjal agro-ecosystem. Proclaim 5SG reduced the overall abundance of arthropod species. Bacillus thuringiensis (Bt) and Tracer 45SC were relatively safe for natural enemies and therefore would be fit well into integrated pest management (IPM) against BSFB of brinjal crop.Int. J. Agril. Res. Innov. & Tech. 8 (1): 55-61, June, 2018